The Attaintment of Healthy Mind Through Islamic Education Between al-Ghazali and Zakiah Daradjat: A Comparative Analysis Study - Setiawan, Muhammad Nurrosyid Huda (Universitas Ahmad Dahlan, 2021)
Zakiah said that religion is a psychological need that must be demanded. In line with him, Ghazali emphasized that the science of religion is the basis of his ethical system. Reaching a healthy mind can be obtained through Islamic education. This is qualitative research with a comparative analysis method. To produce the thoughts of these two scholars are increasingly clearly illustrated. The researcher found that the two figures had the same conclusion in achieving a healthy mind. That is, someone had to look for it through education that emphasized good character. However, they have several different points of thought regarding defining the soul and its relationship to the healthy mind.